Enhanced recovery after adolescent idiopathic scoliosis surgery care pathway: Perioperative strategy to improve outcome - Ph Creyf; N. Parisi; S. Munting; M. Caudron; R. Rossillon; Ch Detrembleur; Munting E (Brain and Spine)
Intro: AIS surgery generates a high inflammatory stress response which might influence the outcome in the perioperative period. Enhanced Recovery After Surgery (ERAS) is a global multidisciplinary care pathway aimed to improve patient's recovery. Research question: The purpose of this article is to expose our actual ERAS protocol for AIS surgery and compare it with the earlier non ERAS management in our institution.Our primary outcome focus on the re-hospitalisation and complications rates at 30 and 90 days postoperatively. Our secondary outcomes focus on the overall morphine consumption, pain scores and side effects during the hospitalisation. Material: We compare the results of the ERAS group (2019–2022) with the previous existing classical care pathway (2017–2019). The data were collected in our standard medical files. Results: Our ERAS care pathway for AIS surgery lead to consequently improve the outcome regarding the VAS scores, the morphine consumption, the LOS and the complication and re hospitalisation rates. Discussion: Regarding our results, ERAS care pathway for AIS surgery appears to be efficient in terms of benefits on complications rates, LOS and opioid consumption.Intrathecal morphine and “anti-inflammatory” anaesthesia provides a good quality of pain management and allows the patient to get up early.A superiority trial might be interesting to highlight the role of the ERAS pathway in AIS surgery.